MORAL JUDGEMENT OF THE CHILDREN AGED 7 AND 13, WITH THE PURPOSE TO TEST THE PIAGET’S THEORY OF MORAL DEVELOPMENT - Novaković, Marina (ACADEMIC REVIEW, 2019)
In this study, a moral judgement of children aged 7 and 13 was examined in order to test Piaget's theory of moral development. For this purpose, two fairy tales were used. The assumptions were that 7-year-olds in fairy tale heroic acts would see a violation, that in assessing their actions they would not take into account their inner motives and would not approve a change in fairy tale rules as opposed to 13-year-olds who should have contrary moral judgments. 120 students were examined, and the data were collected by a clinical interview. The results obtained show that the original expectations were justified, except in the case of the assumption that children age 7 will not take into account the inner motives of the main heroines when reviewing their actions. The results suggest that children of the younger age, when making moral judgments, take into account the motives of the person whose actions they evaluate.